Phosphoribulokinase abundance is not limiting the Calvin-Benson-Bassham cycle in Chlamydomonas reinhardtii - Boisset, Nicolas D.; Favoino, Giusi; Meloni, Maria; Jomat, Lucile; Cassier-Chauvat, Corinne; Zaffagnini, Mirko; Lemaire, Stéphane D.; Crozet, Pierre (Frontiers in Plant Science, 2023)
Improving photosynthetic efficiency in plants and microalgae is of utmost importance to support the growing world population and to enable the bioproduction of energy and chemicals. Limitations in photosynthetic light conversion efficiency can be directly attributed to kinetic bottlenecks within the Calvin-Benson-Bassham cycle (CBBC) responsible for carbon fixation. A better understanding of these bottlenecks in vivo is crucial to overcome these limiting factors through bio-engineering. The present study is focused on the analysis of phosphoribulokinase (PRK) in the unicellular green alga Chlamydomonas reinhardtii. We have characterized a PRK knock-out mutant strain and showed that in the absence of PRK, Chlamydomonas cannot grow photoautotrophically while functional complementation with a synthetic construct allowed restoration of photoautotrophy. Nevertheless, using standard genetic elements, the expression of PRK was limited to 40% of the reference level in complemented strains and could not restore normal growth in photoautotrophic conditions suggesting that the CBBC is limited. We were subsequently able to overcome this initial limitation by improving the design of the transcriptional unit expressing PRK using diverse combinations of DNA parts including PRK endogenous promoter and introns. This enabled us to obtain strains with PRK levels comparable to the reference strain and even overexpressing strains. A collection of strains with PRK levels between 16% and 250% of WT PRK levels was generated and characterized. Immunoblot and growth assays revealed that a PRK content of ≈86% is sufficient to fully restore photoautotrophic growth. This result suggests that PRK is present in moderate excess in Chlamydomonas. Consistently, the overexpression of PRK did not increase photosynthetic growth indicating that that the endogenous level of PRK in Chlamydomonas is not limiting the Calvin-Benson-Bassham cycle under optimal conditions.